Survival, morphological variability, and performance of Opuntia ficus-indica in a semi-arid region of India - Kumar, Sunil; Palsaniya, Dana; Tirumala, Kiran Kumar; Misra, Asim; Ahmad, Shahid; Rai, Arvind Kumar; Sarker, Ashutosh; Louhaichi, Mounir; Hassan, Sawsan; Liguori, Giorgia; Ghosh, Probir Kumar; Govindasamy, Prabhu; et al. (Informa UK Limited, 2023)
Cactus pear (Opuntia ficus-indica (L.) Mill.) can survive extreme environmental condition and is known for its fodder potential in many parts of the world. The morphological diversity of 15 introduced accessions was evaluated at Jhansi, Uttar Pradesh, India. The plants were established in 2013. Survival and nutrient status were evaluated after two years. Above-ground plant height, biomass, primary and secondary cladode numbers, primary and secondary cladode lengths and below-ground root length, weight, and surface area measurements were done six years after cladode planting. Yellow San Cono, White Roccapalumba, and Seedless Roccapalumba survived 100%. The discriminant traits according to principal component analysis were: primary cladodes plant−1 (component loading, 0.87), primary cladodes biomass (0.95), secondary cladodes plant−1 (0.83), canopy width (0.84), and plant biomass (0.92). Hierarchical cluster analysis grouped 15 accessions into two main clusters based on 17 morphological traits. Cluster I showed favorable values for many above- and below-ground morphological traits while Cluster II showed higher performance for root system width, height, and biomass, and primary and secondary cladode numbers. The results indicate that cactus pear accessions have considerable morphological variability and genetic diversity suitable for promotion as alternative fodder resources in semi-arid regions of India.